Study of High-Frequency Pulsating Flow Control Valves - Dongdong Zhang; Yunchen Wu; Kuankuan Zhu; Ruiyi Shi; Jian Ruan; Chuan Ding (Applied Sciences)
Pulsating flow signals are widely used in the fields of dynamic calibration of flow meters and reliability testing of fluid transmission pipelines. A high-frequency pulsating flow control valve is proposed, its structure and working principle are introduced, and its mathematical model is also established. Finally, an experimental platform is built to experimentally verify the performance of the high-frequency pulsating flow signal generation of this flow control valve prototype. When applying sinusoidal flow signals of 1–25 Hz, the amplitude of the output flow starts to decay after 2 Hz, and the frequency corresponding to the decay to −3 dB is about 23.5 Hz. The experimental results show that the valve can effectively generate unidirectional sinusoidal flow with a maximum amplitude of 25 L/min and a frequency of 23.5 Hz.